(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The concept of an employment relationship “limited in time” is known from the beginning of modern labour law. As a result of socioeconomic changes taking place in the XIX and XX-th centuries the role of such contracts also changed considerably as well as the scope of their application due to the evolution of the intended and practicly realized function of these employment contracts. Legal pro- visions concerning employment contracts “limited in time” were developed and their new kinds introduced varying as far as their socio- economic destination and some important elements of their legal characteristics are concerned. In this article evolution of legal provisions and of doctrinal opinions on em- ployment contracts “limited in time” in Poland between the First and Second World Wars and after the Second World War is presented. An attempt was made also to explain the very term “employment contract limited in time” and to specify the scope of its differentiation. Polish labour code knows various kinds of contr- acts belonging to this category: employment contracts concluded for a definite period, contracts for the period required to carry out a specific piece of work, employment contracts concluded for a trial period and for an initial period. Employment contracts “limited in time” are also regulated in several acts of more detailed character still maintained in force. Since the labour code gives a catalogue of different kinds of employment contracts it was necessary to consider whether this is a catalogue of a rigid character or not, in another words, whether statutory classification excludes or allows to combine in one employment contract various construction elements characteristic for separate kinds of employment contracts. This issue was discussed on the basis of article 18 of the labour code. Also, the freedom of contract as far as application of the provisions on employment contracts “limited in time” is concerned and the possibility to conclude such contracts for a long-term periods was presented. Discussion of the binding legal regulation allowed the Author to conclude that the term “employment contract limited in time” contains not one but several statu- tory concepts which in their essence constitute distinct legal institutions. A com- mon feature of these contracts is their limitation in time foreseen by the parties in advance. On the other hand, the differences concerne not only formal elements but also functions fulfilled by a specific kind of an employment contract “limited in time”.